State estimator design and implementation for a multirotor UAV - Kuang, Mingyuan (2017)
Unmanned Aerial Vehicle (UAV) is a flying device very popular today in many industries and capable of carrying out many works. Multirotor, especially quadcopter, is one of the most widely used type. It is fundamental to study the aerodynamics for quadcopters to achieve stable, controllable yet swift flight. In this report, a tool of flight simulation and estimation will be focused on for a better aerodynamics study. The tool is developed in Matlab and Simulink and has a main use of estimating the motion of a quadcopter, with noise reduced. Hence by comparison with ground truth, more theories could be inferred and introduced to the aerodynamics model. One function of the tool is simulation, based on basic quadcopter aerodynamics and other important effects. With cascade PID control, it can simulate a preset motion for a quadcopter. The other function of the tool is estimation, which incorporates mathematic model of Extended Kalman Filter to obtain optimal estimates. The estimation is based on attitude and acceleration information given by sensors at this moment to estimate the velocity of quadcopter at next moment. Furthermore, log test and code transformation was carried out to implement this tool to hardware, so that estimation by quadcopter itself could be achieved.